2002
DOI: 10.1021/jp0130665
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Topological Analysis of the Electronic Density inn-Butonium Cations and Their van der Waals Complexes

Abstract: In this work, the topology of the ab initio electronic density charge, using the theory of atoms in molecules (AIM), developed by Bader, is studied for the n-C 4 H 11 + species, the protonated n-butane. The electronic delocalization that operates through the σ bonds in saturated molecules and specifically in protonated alkanes is studied by means of analysis of the charge density and the bond critical points. This analysis is used in order to establish a relationship among the parameters that determine the sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 25 publications
4
30
1
Order By: Relevance
“…As it was pointed out in the Introduction, carbonium and butonium organic ions are proposed as systems which possess complex patterns of 2e-3c bonding interactions. 6,7 Our results indicate that these bonding interactions have different characteristics from those well known electron deficient boron hydrids and hence they admit an important new feature which induces a wider interpretation of the rule. To this end, the information obtained may be interpreted as it is not necessary that both views of the rule, i.e., the local and the nonlocal conditions, ought to be satisfied in order to recognize a 2e-3c interaction.…”
Section: Computational Details Results and Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…As it was pointed out in the Introduction, carbonium and butonium organic ions are proposed as systems which possess complex patterns of 2e-3c bonding interactions. 6,7 Our results indicate that these bonding interactions have different characteristics from those well known electron deficient boron hydrids and hence they admit an important new feature which induces a wider interpretation of the rule. To this end, the information obtained may be interpreted as it is not necessary that both views of the rule, i.e., the local and the nonlocal conditions, ought to be satisfied in order to recognize a 2e-3c interaction.…”
Section: Computational Details Results and Discussionmentioning
confidence: 73%
“…Electron deficient compounds like boron hydrids give rise to important complex patterns of bonding which has been associated to two-electron three-center interaction mechanisms. [1][2][3][4][5] These multi-center interactions are known to appear in a wide variety of molecular systems as organic ions, [6][7][8] metallic and non-metallic clusters among others. 9 Nevertheless, the different types of molecular systems, i.e., the boron hydrids and the carbonium ions show different patterns within this type of interactions characterizing the bonding interactions and thus constitute a landmark for comparative detailed studies about them.…”
Section: Introductionmentioning
confidence: 99%
“…28 The quantum theory of atoms in molecules (QTAIM) was used to study many carbonium ions, such as proponium and 2-norbornyl cations. [29][30][31][32][33][34][35][36][37][38][39] In this work we show that the QTAIM can be used to evaluate whether a carbocation is classical or not. It is also possible to determine the order of σ or π delocalization within the similar group of cations.…”
Section: Introductionmentioning
confidence: 78%
“…These species contain three-center two-electron bonds (3c−2e) and can be generated upon the insertion of a proton or a carbenium ion into the C−H or C−C bonds. The group of Jubert has analyzed the electron distribution of C 3 H 9 + , n -C 4 H 11 + , , and i -C 4 H 11 + . They concluded that the stability of these protonated species depends fundamentally on the way in which the charge of the cation is delocalized around the 3c−2e bonds.…”
Section: 24 Carbocationsmentioning
confidence: 99%